EMOTIONAL EXHAUSTION AND QUALITY OF LIFE AMONG RESCUE WORKERS: MODERATING ROLE OF SOCIAL SUPPORT - Saheem, Farhan; Ayub, Sumaira (Journal of Postgraduate Medical Institute, 2023)
Objective: To determine the moderating role of social support in determining the relationship between emotional exhaustion and the quality of life among rescue workers. Methodology: Correlational research was conducted. Purposive sample of 170 rescue workers as calculated by as calculated by G power formula. The age range of the sample was 22-46 years (M = 31.7, SD = 5.05). The data were collected from rescue offices of three districts of Punjab including Layyah Bhakkar, Jhung and one district Dera Ismail Khan of Khyber Pakhtunkhawa using demographic information sheet and related assessment measures. Data were analyzed using SPSS-26. Pearson product moment correlation and moderation through multiple hierarchical regression analyses to test the hypotheses. Results: Emotional exhaustion found to be positively related to secondary traumatic stress (r= 0.24, p < 0.01) and burnout (r= 0.21, p < 0.01) subscales of quality of life in rescue workers. It was also found that social support showed negative relationship with secondary traumatic stress (r= -0.22, p < 0.01) and burnout (r= -0.36, p < 0.01), while positive relationship with compassion satisfaction (r= 0.22, p < 0.01). Further, emotional exhaustion positively (B =.22, p < .01) and family support negatively (B =- .21, p <.01) predicted the burnout and secondary traumatic stress. The results showed significant interaction effect of family support and emotional exhaustion (B = -.97, p < .05) in predicting secondary traumatic stress in rescue workers. Conclusion: It is concluded that emotional exhaustion has an adverse effect on the quality of life of rescue workers, and this influence can be moderated and improved through the presence of social support.